The ‘why’ and ‘what for’ of participation in tourism activities: travel motivations of people with disabilities - Moura, Andreia (2022)
The aim of this study is to identify the motivations that lead people with disabilities (PwD) to make the decision to participate in tourism and to ascertain whether there are differences in these motivations between PwD with and without tourism experiences. To achieve this goal, a guiding research model was created based on the mechanism of selfdetermination theory (SDT). A mixed methodology approach was used. First, semi-structured interviews were conducted with a sample of PwD living in Portugal (N = 28). Second, a questionnaire was administered to a sample of Portuguese with disabilities (N = 348). The results obtained highlight that PwD are motivated to participate in tourism activities, mainly because of the benefits they expect to gain from these experiences. However, a great number have never had the possibility of participating in tourism activities. Intrinsic or self-determined motivations such as pleasure, increased knowledge, well-being and personal development, stand out. Moreover, PwD who have never had the opportunity to participate in tourism activities perceive more benefits than those who have already participated. The paper ends with the theoretical and practical implications, the limitations and future research to increase knowledge in an area that has been little explored in the literature.